The meningeal lymphatic vessels and the glymphatic system: Potential therapeutic targets in neurological disorders. Issue 8 (August 2022) - Li, Gaowei; Cao, Yi; Tang, Xin; Huang, Jianhan; Cai, Linjun; Zhou, Liangxue
The recent discovery of the meningeal lymphatic vessels (mLVs) and glymphatic pathways has challenged the long-lasting dogma that the central nervous system (CNS) lacks a lymphatic system and therefore does not interact with peripheral immunity. This discovery has reshaped our understanding of mechanisms underlying CNS drainage. Under normal conditions, a close connection between mLVs and the glymphatic system enables metabolic waste removal, immune cell trafficking, and CNS immune surveillance. Dysfunction of the glymphatic-mLV system can lead to toxic protein accumulation in the brain, and it contributes to the development of a series of neurodegenerative disorders, such as Alzheimer's and Parkinson's diseases. The identification of precise cerebral transport routes is based mainly on indirect, invasive imaging of animals, and the results cannot always be applied to humans. Here we review the functions of the glymphatic-mLV system and evidence for its involvement in some CNS diseases. We focus on emerging noninvasive imaging techniques to evaluate the human glymphatic-mLV system and their potential for preclinical diagnosis and prevention of neurodegenerative diseases. Potential strategies that target the glymphatic-mLV system in order to treat and prevent neurological disorders are also discussed.